Efektivitas Micro-Influencer Hijrah di Media Sosial dalam Membentuk Karakter Sosial-Keagamaan Generasi Z - Muhammad Fadel Malik Sulaiman; Muhammad Nasya Abdu; Ivan Kurniawan; Roni Hidayat (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The current shift in the search for role models among Generation Z has moved away from traditional authority figures toward content creators on social media platforms. This study aims to investigate the effectiveness of hijrah micro-influencers on social media platforms such as Instagram and TikTok in influencing and shaping the socio-religious character of Generation Z, bypassing the formal boundaries of traditional pulpit dawah. Applying a qualitative method with a Qualitative Content Analysis approach, this research focuses on uploaded content, visual narratives, and the interactions occurring within the comment sections. The research findings indicate that emotional proximity and the perception of “shared experiences” are the primary keys to the effectiveness of their dawah message delivery. The text and visuals produced are consistently proven to reflect the formation of a new religious character that is more open, an increased social awareness, and the implementation of a digital religious identity that is perceived as modern yet remains devout. Keywords: Micro-Influencers, Hijrah Phenomenon, Generation Z, Socio-Religious Characteristics, Content Analysis. Abstrak Pergeseran kiblat pencarian figur teladan di kalangan Generasi Z kini beralih dari figur otoritas konvensional ke para pembuat konten di media sosial. Penelitian ini bertujuan untuk menganalisis efektivitas micro-influencer hijrah di media sosial (Instagram dan TikTok) dalam memengaruhi dan membentuk karakter sosial-keagamaan Generasi Z tanpa melalui sekat-sekat formalitas dakwah mimbar. Menggunakan metode kualitatif dengan pendekatan Analisis Isi Kualitatif (Qualitative Content Analysis), penelitian ini berfokus pada teks unggahan, narasi visual, serta dinamika interaksi yang terbangun di kolom komentar. Hasil penelitian menemukan bahwa kedekatan emosional (parasocial interaction) dan persepsi “kesamaan nasib” (relatability) menjadi faktor utama efektivitas pesan dakwah. Stimulus teks dan visual yang diproduksi secara konsisten terbukti merepresentasikan pembentukan karakter keagamaan baru yang lebih inklusif, peningkatan kepedulian sosial, serta adopsi identitas keagamaan digital yang dianggap modern namun tetap taat. Kata kunci : Micro-Influencer, Fenomena Hijrah, Generasi Z, Karakter Sosial-Keagamaan, Analisis Isi.